The dermal deposits in the finger of the Holy Roman Emperor Charles I of Spain and V of Germany - Fernandez-Flores, Angel; Fonseca, Eduardo (Frontiers in Medicine, 2024)
Charles I of Spain and V of Germany was one of the most prominent figures in Christendom. The vast empire ruled by the monarch extended across multiple continents. However, the final years of his life were overshadowed by depression and incapacitating joint degeneration, leading him to retire to the Monastery of Yuste in Cáceres, Spain. It was there that he contracted malaria, a disease that ultimately claimed his life. In this article, we evaluate the studies conducted on one of his mummified fingers to confirm the presence of malaria and investigate the cause of his joint degeneration, which was attributed to intense deposits of uric acid.